TEKS DAN ILUSTRASI IKLAN DEWASA DI LAMAN GAMES ONLINE - Sariati, Nur (JURNAL ILMU BUDAYA, 2017)
This study aims to (1) describe the delivery of text and illustrations pornography in adult ads in online games page. (2) to categorize the modes used in the ad text in a page of online games. The results showed (1) There are two methods of delivery of pornography in the text and illustrations of ads on a page of online games, which bluntly and obscurely. Submission of pornography openly seen from the meaning of denotation and connotations, while the delivery of pornographic meaning vaguely seen from the meaning in connotation. The suggestive power of visualization, the ability of sex organs and sexual activity, stimulation of the sex organs, and the depiction of power or virility that encourages libido are shown in faintly visible pornographic depictions. (2) there are several classes of modes in the ad text pages online games, namely: declarative, imperative and introgatif.